2002
DOI: 10.1078/0932-4739-00817
|View full text |Cite
|
Sign up to set email alerts
|

On the life cycle of Aggregata eberthi and observations on Aggregata octopiana (Apicomplexa, Aggregatidae) from Galicia (NE Atlantic)

Abstract: Stages of merogony of a coccidian parasite were commonly observed during histological examination of the digestive tract of 7 crustacean species from Galician coastal waters. Study of the fine structure of these merogonial stages by transmission electron microscopy revealed the presence of a typical apicomplexan apical complex. Newly hatched Sepia officinalis obtained from egg masses, cultured in 3 separate tanks, were fed with three parasitised prawn species in infection experiments. Cuttlefish fed with Palae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
1
16
1
3
Order By: Relevance
“…In order to understand the finding of Aggregata-infected squid, it would be necessary carry out a detailed study of the life-cycle of Aggregata spp., especially in terms of the identification of the intermediate host, the mechanism of squid infection and the level of host-specificity. In fact, one of the reasons for the selective infection of the SW Atlantic Ocean squid studied may be the great specificity of these parasites in relation to the cephalopod definitive host, as had already been described for other Aggregata spp., such as A. octopiana (Schneider, 1875) and A. eberthi (see Porchet-Henneré & Richard, 1971;Porchet-Henneré et al, 1981;Gestal et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…In order to understand the finding of Aggregata-infected squid, it would be necessary carry out a detailed study of the life-cycle of Aggregata spp., especially in terms of the identification of the intermediate host, the mechanism of squid infection and the level of host-specificity. In fact, one of the reasons for the selective infection of the SW Atlantic Ocean squid studied may be the great specificity of these parasites in relation to the cephalopod definitive host, as had already been described for other Aggregata spp., such as A. octopiana (Schneider, 1875) and A. eberthi (see Porchet-Henneré & Richard, 1971;Porchet-Henneré et al, 1981;Gestal et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Stages of merogony of Aggregata spp., a coccidian parasite, have been reported in Palaemon adspersus Rathke 1837 and P. elegans Rathke 1837 (Gestal et al 2002), and P. adspersus could be experimentally infected with the White Spot Syndrome Virus (WSSV) (Corbel et al 2001). …”
Section: Introductionmentioning
confidence: 98%
“…Sporozoites migrate through the midgut epithelium to the submucous connective tissue, where they grow and become meronts. Finally, meronts generate merozoites by schizogony in the same way as the sporozoites develop in the cephalopod host (Hochberg 1990, Gestal et al 2002a. Experimental infections have concluded that coccidians of the genus Aggregata show a high degree of specificity in the definitive host; however, lower specificity was observed in the intermediate crustacean host (Gestal et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual stages (gamogony and sporogony) occur in the digestive tracts of cephalopods, the definitive hosts, and asexual stages (merogony) in the digestive tracts of crustaceans, the intermediate hosts (Dobell 1925, Gestal et al 2002a. The union of a microgamete and a macrogamete in the digestive tract of a cephalopod produces a zygote, which becomes an early sporont with numerous nuclei.…”
Section: Introductionmentioning
confidence: 99%